1992
DOI: 10.3171/jns.1992.77.1.0069
|View full text |Cite
|
Sign up to set email alerts
|

Scoliosis in pediatric Chiari malformations without myelodysplasia

Abstract: A prospective study was undertaken in 1985 to better understand how the surgical manipulation of hindbrain herniation affected abnormal spinal curvature. Eleven patients under 16 years of age with Chiari malformation (not associated with myelodysplasia) and scoliosis of at least 15 degrees were studied. The mean curve angle at the time of original treatment was 29 degrees, with the convexity to the right in seven patients. The curvature was rapidly progressing in four patients. The most common presenting signs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
2
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(46 citation statements)
references
References 33 publications
0
43
2
1
Order By: Relevance
“…Further, intramedullary tumors can present with scoliosis without neurological deficits [7]. However, the mechanism by which a syringomyelia or a Chiari malformation type 1 (CM-1) causes the scoliosis is poorly understood [11,12]. It has been suggested that an asymmetrically expanding syringomyelia causes pressure and injures the lower motor neurons in the gray matter of the anterior horn innervating the trunk muscles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, intramedullary tumors can present with scoliosis without neurological deficits [7]. However, the mechanism by which a syringomyelia or a Chiari malformation type 1 (CM-1) causes the scoliosis is poorly understood [11,12]. It has been suggested that an asymmetrically expanding syringomyelia causes pressure and injures the lower motor neurons in the gray matter of the anterior horn innervating the trunk muscles.…”
Section: Discussionmentioning
confidence: 99%
“…This imbalance of the paravertebral muscles may presumably cause the scoliosis [3]. Another explanation could be that patients with CM-1 have an equilibrium dysfunction disturbing the postural reflex system and causing scoliosis [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…In some papers, the authors distinguish between "paralytic scoliosis" and "idiopathic scoliosis" ]1, 8,11,15]. "Paralytic scoliosis" is observed with severe dysraphism in children and it is always a very evolutive scoliosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors assume that the location of syringomyelia and the severity of neurological involvement are not related to the magnitude or location of the scoliosis [8,11]. Considering the coexistence between scoliosis and syringomyelia, Aboulker concludes that scoliosis may predispose a patient to syringomyelia, because of the appearance of radicular lesions and the modifications of the spinal CSF balance that appear on the convexity of scoliosis [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation